Adolescent Perceptions of an Interactive Mobile Application to Respond to Teen Dating Violence - Debnam, Katrina J. (Journal of interpersonal violence, 2021)
Although research and intervention efforts in the United States have aimed to reduce teen dating violence (TDV), 10-year prevalence estimates suggest that TDV persists. Safety planning is an advocated intervention to reduce intimate partner abuse; yet, safety planning services for adolescents have not been systematically developed or tested. Personalized safety planning interventions that reflect teens’ immediate risk, priorities, and resources may be a key prevention and empowerment tool. Thus, the current study examined adolescent perceptions of an existing safety planning app, myPlan. A small convenience sample of adolescents participated in focus groups. Focus groups investigated the feasibility of an app for TDV intervention and elicited feedback on how apps can better assist adolescents experiencing dating violence. Qualitative content analysis was used to identify themes and patterns in the data. The following themes emerged: (a) careful and thoughtful inclusion of diverse adolescents, (b) capturing unique safety dilemmas encountered by adolescents, (c) clarifying the signs of an unhealthy and abusive relationship, and (d) resources for immediate help. Adolescents were thoughtful in their consideration of the myPlan app and articulated specific ways in which future applications could be more responsive to their lived experiences and challenges. Mobile app or electronic interventions that are developed with an eye toward empowering adolescents to understand how abusive behaviors may manifest in their relationships, weigh the risk and benefits of intervening, and are informed about local resources available to them for help may be most successful in reducing TDV.